Factors Affecting Audit Delay Moderated By Profitability of Companies in the Jakarta Islamic Index - Ahmad Ulil Albab Al Umar; Herninda Pitaloka; Anava Salsa Nur Savitri; Nur Kabib (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
The financial statements are an important part of the stakeholders or stakeholders as a reference in making investments. This study aims to analyze the effect of company size, auditor opinion, and age of the company on audit delay with profitability as a moderating variable. This research is a quantitative research. Data analysis in this study uses multiple linear regression with EViews 11. The population in this study is all companies listed on the Indonesian Sharia Stock Index in 2015-2018. The sample in this study were 30 companies listed on the Jakarta Islamic Index. The data used in this research is secondary data. The results in this study showed that company size and auditor's opinion no affect the audit delay, while the age of the company influences to audit delay. Company size, auditor opinion, and age of the company are not able to moderate audit delay. This shows that profitability is not able to moderate the three variables.